ANALISIS NILAI KARAKTER DISIPLIN DALAM PEMBELAJARAN PKN PADA SISWA KELAS V SD NEGERI 89 PALEMBANG - Hesti Nur Prihatini; Ramanata Disurya; Tanzimah (STKIP Subang, 2024)
This study aims to find out how to apply the value of discipline character in learning PKn in grade V students of SD Negeri 89 Palembang. This research uses a qualitative method, the research technique is carried out by observation, interviews, questionnaires and documentation. Data analysis techniques are using data reduction, data presentation, and data verification or conclusions. The results of this study were carried out in accordance with the indicators. The first indicator comes on time, the second indicator completes the tasks for which he is responsible, the third indicator obeys school and class rules, the fourth indicator collects assignments on time, the fifth indicator is neatly dressed. This indicator is the value of discipline character in PKn learning which is determined to grade V students of SD Negeri 89 Palembang with a total of 22 students, 15 students are included in the very good category, 4 students are included in the good category, and 3 students are included in the sufficient category. This happens because teachers really apply the value of discipline character in PKn learning and teachers explain and emphasize the importance of applying discipline character values. Teachers also reward students who have applied the value of discipline character in PKn learning